Orchestrating Austerity: Impacts & Resistance - Duarte, Filipe (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2015)
Donna Baines & Stephen McBride (Eds.), Halifax & Winnipeg: Fernwood Publishing, 2014.